2023
DOI: 10.3390/smartcities6050112
|View full text |Cite
|
Sign up to set email alerts
|

The Use of the Smart Technology for Creating an Inclusive Urban Public Space

Mohammed Itair,
Isam Shahrour,
Ihab Hijazi

Abstract: This paper strives to enhance the inclusivity of urban public spaces, which play a crucial role in providing essential services for all citizens, including community building, physical and mental well-being, social interaction, civic engagement, citizen participation, and economic vitality. Despite the importance of these spaces, as recognized by the UN’s 2030 sustainability goals, the 2023 UN sustainable development report and scholars have drawn attention to their low availability, particularly for low-incom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The evaluation factors includes various factors, such as the street network, functional density, diversity, and accessibility [37,38]. Some studies evaluate public space vitality based on spatial environmental amenities, including sanitation facilities, fitness and entertainment facilities, and facilities for different age groups [39,40]. Additionally, some studies have also analyzed the vitality of urban green spaces and found that factors such as green space area and external and internal spatial characteristics are key elements influencing the vitality of public spaces [41].…”
Section: Research On the Vitality Theory Of Public Spacementioning
confidence: 99%
“…The evaluation factors includes various factors, such as the street network, functional density, diversity, and accessibility [37,38]. Some studies evaluate public space vitality based on spatial environmental amenities, including sanitation facilities, fitness and entertainment facilities, and facilities for different age groups [39,40]. Additionally, some studies have also analyzed the vitality of urban green spaces and found that factors such as green space area and external and internal spatial characteristics are key elements influencing the vitality of public spaces [41].…”
Section: Research On the Vitality Theory Of Public Spacementioning
confidence: 99%
“…Social media applications such as Facebook, Twitter and Instagram, alongside web-based gaming such as Second Life and the rise of mobile devices, are providing new means and platforms for online interaction. In the realm of planning, such platforms can facilitate community organisation and engagement in decision-making processes (see [2,[4][5][6][7]) as part of a general prerogative for 'smart' and inclusive cities [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have examined women's perceptions and gender differences in urban experiences [17][18][19]. They have also looked at women's participation and the gender gap in politics [10,20,21], the economy [22,23], and technology [24][25][26]. However, no single study explicitly defined the concept of "women-inclusive cities".…”
Section: Introductionmentioning
confidence: 99%